Problem odniesienia obrazów halucynacyjnych pojawiających się w kontekście doswiadczeń duchowych - Nowak, Szymon (Hybris, 2016)
The goal of this article is to discuss a theory of reference for hallucinatory experiences. Firstly, my paper will be concerned with the theory of perception underlying common definition of hallucination. Secondly, I will present three main theories of reference for experiences given in different kinds of altered states of consciousness. These three theories are: neuroscientific, supranaturalistic and psychoanalytical. Consecutively I will present arguments for maintaining that classical theories are examples of semiotic reductionism. In the main part of this paper I will present an anti-reductionist framework for a reference of hallucinatory experience, based on a phenomenological analysis of particular kind of experience not caused by external stimulus, that is, mystical experience. This anti-reductionistic theory will claim that a proper reference of certain kinds of altered states of consciousness is a true symbol.